Strategic risk management in public library services: Approaches to prioritization and mitigation - Mehdi Rahmani, (Malaysian Journal of Library and Information Science, 2025)
Public libraries face many challenges in maintaining their services, especially in a rapidly evolving technological and economic environment. This study identifies and prioritises the main risks impacting public library services in Iran and proposes strategic solutions to address these challenges. The study is based on a meta-synthesis of scientific literature, the fuzzy Delphi technique for expert evaluation and Chang’s Fuzzy Hierarchy Analysis to rank the most important risks. Field observations were conducted in several provinces of Iran to validate the results and develop region-specific strategies. The study identified 75 risks, which were categorised into nine main groups. The greatest risk was the loss of access to digital resources due to economic sanctions and financial restrictions, followed by competition from search engines and alternative digital information platforms. The expert’s evaluation emphasised that technological limitations and insufficient funding are the most pressing threats to the sustainability of public libraries. To overcome these challenges, the study recommends improving technological infrastructure, fostering collaboration between libraries, implementing innovative outreach programmes and diversifying financial support strategies. The findings emphasise the urgent need for public libraries to address digital transformation and strategic planning to remain relevant in digital and economically constrained environment. As public libraries worldwide face similar financial, technological and operational risks, this study contributes to the global library policy discussion by offering a scalable risk assessment model that is applicable to different library systems. These findings can guide decision-makers in library governance, digital transformation policies and strategies for sustainable access to knowledge at national and international levels.